Crystalline structures in foams: guided mechanical self-assembly of bubbles in fiber arrays - Marwan Chammouma; Manon Jouanlanne; Antoine Egelé; Damien Favier; Jean Farago; Aurélie Hourlier-Fargette (JPhys Materials)
Spontaneous mechanical self-assembly of monodisperse bubbles generally leads to disordered foams at low density. Producing crystalline structures requires specific care: for example, Kelvin foams—periodic assemblies of bubbles arranged on a body-centered cubic lattice—are a typical example of a structure which is challenging to obtain experimentally, despite it being a local minimum of energy. Here we show how bubbling in different arrangements of fibers enables to control foam architectures through a guided mechanical self-assembly of bubbles: for optimal ratios of bubble size to fiber spacing, Kelvin and hexagonal close packing crystalline foams are formed in square and hexagonal fiber arrays, respectively. The long-range crystalline architectures achieved in samples spanning hundreds of bubbles are then quantified through a theoretical approach analysing the orientational order in the samples. This methodology, based on the decomposition of strut orientations via spherical harmonics, is inspired by the so-called Steinhardt’s coefficients , developed for quantifying rotational order in 3D liquids. Beyond the achievement of architecting liquid foam structures, our work demonstrates that the obtained ordering persists upon solidification of initially liquid polymeric foams, using alginate and polyurethane foams in nylon fiber arrays as model systems. The mechanically guided self-assembly of bubbles offers an attractive alternative to additive manufacturing to generate highly ordered architected polymeric materials.